Insights into the effects of epoxy resin infiltration on powder aging issue induced by powder recycling in powder bed fusion of Nylon12 materials - Anfu Guo; Jin Wang; Rongji Tang; He Kong; Dekun Kong; Peng Qu; Shaoqing Wang; Hongbing Wang; Yingbin Hu (Journal of Materials Research and Technology, 2023)
In a powder bed fusion (PBF) process where powder bed preheating is needed, the powder bed will be subjected to an aging issue, which limits the reuse of powders. In response to the powder aging issue and to recycle powders, extensive attention has been attracted to study powder aging mechanisms in PBF to explore potential solutions. In this investigation, we have studied the aging mechanisms and proposed an epoxy resin solution (EP) infiltration method to mitigate side effects of powder aging in PBF-sintered nylon12 (PA12) specimens. Particularly, a comprehensive study on effects of powder recycling, building directions, and EP infiltration on microstructure characterizations, part quality, as well as thermal and mechanical properties of PBF-sintered PA12 specimens has been presented, for the first time. The quantitative relationships between sintering window width and warpage degree have been developed. A finite element analysis method has been utilized to learn stress distribution and concentration in PBF-sintered PA12 specimens and to predict fracture features. An insight into the strengthening effects induced by the EP infiltration at an atomic level has been provided by conducting molecular dynamic simulations.